2016
DOI: 10.1007/s11145-015-9617-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of language specific factors on early written composition: the role of spelling, oral language and text generation skills in a shallow orthography

Abstract: Spelling skills have been identified as one of the major barriers to written text production in young English writers. By contrast oral language skills and text generation have been found to be less influential in the texts produced by beginning writers. To date, our understanding of the role of spelling skills in transparent orthographies is limited. The current study addressed this gap by examining the contribution of spelling, oral language and text generation skills in written text production in Italian be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 43 publications
6
34
0
2
Order By: Relevance
“…In the present work, we examined the ability to construct an intertext model and an integrated mental model by asking children to organize their mental representation around an argument schema expressed through a short essay. The latter is considered as a comprehensive measure and hybrid task; it requires an understanding of the information presented in documents and also the identification of an organizational structure to integrate information and the translation of ideas into written texts (Arfé, Dockrell, & De Bernardi, ; Hayes & Flower, ; Mateos & Solé, ). We chose to use this demanding and complex task because it requires knowledge transformation to a greater extent than other kinds of tasks (i.e., verification tasks) and seems to be a better measure of deep‐level understanding of multiple documents (Bråten, Anmarkrud, et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In the present work, we examined the ability to construct an intertext model and an integrated mental model by asking children to organize their mental representation around an argument schema expressed through a short essay. The latter is considered as a comprehensive measure and hybrid task; it requires an understanding of the information presented in documents and also the identification of an organizational structure to integrate information and the translation of ideas into written texts (Arfé, Dockrell, & De Bernardi, ; Hayes & Flower, ; Mateos & Solé, ). We chose to use this demanding and complex task because it requires knowledge transformation to a greater extent than other kinds of tasks (i.e., verification tasks) and seems to be a better measure of deep‐level understanding of multiple documents (Bråten, Anmarkrud, et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these factors might be tapping into similar cognitive processes, including advanced oral language skills and working memory. Both are mainly genetically influenced in middle school (Little et al, 2015; Hayiou-Thomas, Dale, & Plomin, 2012) and have been shown to be predictive of writing (Arfe, Dockrell, & De Bernardi, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…However, the National Assessment of Educational Progress (NAEP; 2002, 2011; NAEP is the largest nationally representative assessment of what American students know and can do in various subjects) results show that only 28% of fourth graders and 27% of eighth graders perform at or above proficient level in writing. Concerns over low levels of writing achievement in elementary and middle school, together with evidence that children with writing disabilities are at greatly enhanced risk of difficulties in reading and math (Mayes & Calhoun, 2006; Sumner, Connelly, & Barnett, 2013), have motivated a large body of work to identify the sources of individual variability in writing (Abbott & Berninger, 1993; Arfe, Dockrell, & De Bernardi, 2016; Babayigit, 2014; Berninger et al, 1992, 2002; Graham, Berninger, Abbott, Abbott, & Whitaker, 1997; Graham, McKeown, Kiuhara, & Harris, 2012; Kim et al, 2011; Kim, Al Otaiba, Folsom, Greulich, & Puranik, 2014; Kim, Al Otaiba, Wanzek, & Gatlin, 2015; Kim, Park, & Park, 2013; Limpo & Alves, 2013; Olinghouse, 2008; Olinghouse, Graham, & Gillespie, 2015). One line of research that would further clarify variability in writing in elementary and middle school is investigating the etiological (genetic and environmental) factors associated with individual differences in writing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivation was more recently included as a variable in the equation of age x writing about the writing skills and the levels of achievement among different ages (Pajares 2003;Schwabe et al 2015). Spelling skills and oral grammar have been examined as the most influential previous skills for early writing of individuals characterized according to different age groups (Arfé et al 2016). Another perspective for the analysis of the age factor and its influence is the age of migration and its impact on L2 proficiency (Guven and Islam 2015).…”
Section: Introductionmentioning
confidence: 99%